Roland Barthes Semiotic Analysis in Turning Red Movie - Tanzil, Jessica Olivia; Andriano, Stefanus (Communicare : Journal of Communication Studies, 2023)
Turning Red, a Disney Pixar animated film from 2022, tells the sudden transformation of Mei, a 13-year-old teenager who turns into a red panda when her emotions burst. The film highlights the complex relationship between Mei and her mother, focusing on interpersonal communication as a cause of conflict. This research utilizes Roland Barthes' semiotics theory to analyze symbols and meanings in the Mother-Child communication. Using a qualitative descriptive method, the analysis is conducted on 19 scenes from the film. The results emphasize the importance of effective communication and conflict management, along with the role of parenting styles in influencing the Mother-Child relationship.